Quantum Dot Single Electron Transistor Structure Formation Using E-Beam Lithography - Uda, Hashim, Prof. Dr.; Zul Azhar, Zahid Jamal, Prof. Dr.; Samsudi, Sakrani, Prof. Dr.; Sutikno, Madnarski (C. I. S. Network, 2010)
Prof. Dr. Uda Hashim and his team won bronze at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.